How Does Bank Competition Affect Systemic Stability? - Anginer, Deniz; Demirguc-Kunt, Asli; Zhu, Min (2012)
Using bank level measures of competition and co-dependence, the authors show a robust positive relationship between bank competition and systemic stability. Whereas much of the extant literature has focused on the relationship between competition and the absolute level of risk of individual banks, they examine the correlation in the risk taking behavior of banks, hence systemic risk. They find that greater competition encourages banks to take on more diversified risks, making the banking system less fragile to shocks. Examining the impact of the institutional and regulatory environment on systemic stability shows that banking systems are more fragile in countries with weak supervision and private monitoring, with generous deposit insurance and greater government ownership of banks, and public policies that restrict competition. Furthermore, lack of competition has a greater adverse effect on systemic stability in countries with low levels of foreign ownership, weak investor protections, generous safety nets, and where the authorities provide limited guidance for bank asset diversification.